The Influence of Health Technologies in Managing Chronic Illness: Systematic Review - Almutairi, Abdulwahab Meteb Saif; Alyousef, Hessa Abdulatif; Alarafah, Fahad Mohammed; Alnasser, Murad Nasser; Aldohaiman, Saleh Ali; Almutairi, Abdulatif Meteb; Alameri, Rana Ali; Lopez, Rowena Deliva; ALHUSSAIN, GHADEER FOUAD; ALDALBAHI, AHOOD AWADH; et al. (Journal of Posthumanism, 2024)
Objectives: This research aims to find the influence of health technologies in managing chronic illness through a systematic review. Method : structured around a comprehensive systematic review, aiming to gather, assess, and synthesize empirical data on the impact of health technologies on chronic disorder management. Utilizing databases such as PubMed, Medline, Scopus, Google Scholar, and Web of Science, a meticulous search strategy was crafted using relevant keywords and Medical Subject Headings (MeSH) terms. To ensure inclusivity, manual searches of reference lists were also performed. The review was confined to English-language articles published between 2013 and 2023.Result: Health technologies, including mobile applications, telemedicine, and artificial intelligence, were found to have a significant positive impact on the self-management and monitoring of chronic conditions. Patients reported enhanced convenience, a sense of control over their health, and identifying early signs of exacerbation in chronic illnesses, hence facilitating proactive healthcare and mitigating the need for hospital admissions.Conclusion: Healthcare organizations aiming to adopt or improve the utilization of health technology for managing chronic illnesses should give priority to user-centered design and data protection. Adapting digital solutions to be user-friendly and easily available to individuals of all ages and technological abilities is of utmost importance.